2013
DOI: 10.4236/aid.2013.33033
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TTV-ORF2 Protein for Detection of Anti-TTV IgG Antibodies in Human Sera

Abstract: The present study describes the cloning and expression of ORF-2 region of TTV genome and the use of expressed peptide in developing immunoassay for detection of anti-TTV antibodies in serum. Presence of TTV-DNA in serum was detected by PCR amplifying N-22 region of ORF-1 of TTV genome. This was followed by genotyping of TTV by RFLP using N-22 amplicon. Using genotype-1 positive serum as the source of TTV, the ORF-2 region was amplified by PCR and subsequently cloned and expressed in pET-19b vector. The express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Serum from a known TTV-positive sample was tested and this produced a clear spot on the strip after development with the DAB substrate solution. No spot was observed on the strip when a known TTV-negative sample [32,30] was used in the assay as the primary antibody. The present assay was used to detect anti-TTV antibodies in a panel of sera from patients with liver and renal diseases as well as healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Serum from a known TTV-positive sample was tested and this produced a clear spot on the strip after development with the DAB substrate solution. No spot was observed on the strip when a known TTV-negative sample [32,30] was used in the assay as the primary antibody. The present assay was used to detect anti-TTV antibodies in a panel of sera from patients with liver and renal diseases as well as healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although similar attempts were made in the past using various subgenomic regions of TTV-DNA, including ORF-1 [40,43,44] and ORF-2 [15,28,32]; however, we envisaged that N22, being a conserved region, could be a better subgenomic region for use in the development of immunoassay. Furthermore, all of the studies reported so far are based on genotype 1 since it is highly prevalent globally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations